José Martí, fine sand. Archive and reading in a short story by Marcial Gala (Anclajes, 2021)
The article addresses the problem of the reading and archive of José Martí in the short story “Three months before Pilar's death” (2010), by Marcial Gala. Towards the end of the 20th century, the Cuban intellectual field made breaking with the national hero a requirement for its own legibility. Gala is a contemporary of these debates and the short story presents similar themes to other narratives of the Special Period, as well as a critical treatment of the figure of Martí. Nevertheless, it enables an exploration of the remainders of Martí’s archive, organizing and systematizing his discourse in different, though not canonical fashion. These archival operations are put forward through two actions: detonating Martí’s poem “Los zapaticos de rosa”, published in La Edad de Oro in 1889, reorganizing its fragments and placing the exercise of reading at its center.
Keywords: José Martí; cuban archive; reading; cuban narrative; latin american modernist poetry